Perceptions of librarians towards the adoption of embedded librarianship in Tanzania - Mushi, Carren; Mwantimwa, Kelefa; Wema, Evans (University of Dar es Salaam Library Journal, 2021)
Academic libraries in Tanzania have not fully adopted or embraced embedded librarianship as an innovative approach to enhance library service delivery. To gain understanding on the adoption of embedded librarianship, the present study explored the librarians' perceptions towards the adoption of embedded librarianship approach in academic libraries in Tanzania. The study mainly employed exploratory research design blended in a mixed research approach where both quantitative and qualitative aspects were used. A total of 166 librarians from six university libraries filled the questionnaire while 6 directors were interviewed. Statistical Product for Service Solutions (SPSS) version 21 was used to perform descriptive statistics. The study revealed librarians' positive perceptions on the adoption of embedded librarianship in academic libraries. Strengthening librarians and user partnership is an important mechanism to enhance library service delivery. Building strong collaboration between library and faculties through MoU, and enhancing librarians' competencies in teaching, research, communication, ICT applications are necessary for effective adoption of embedded librarianship.